National Housing Policies and Gender Issues: Reflections on Argentina’s ‘Habitar en Igualdad’ Program - da Costa, Yuri Nascimento Paes; de Lima, Carlos Henrique Magalhães (Advances in Social Sciences Research Journal, 2024)
Social rights are not easily given as they are built through processes of struggle, mostly led by organized collectives and social movements in situations of vulnerability or imminent loss of rights and lives. The right to housing is included in this category of social rights that needed to be achieved based on demands, especially in Latin America. This article aims to reflect on public policies and gender issues in Argentina, based on the analysis of the interministerial program ‘Habitar en Igualdad’. To this end, we base our discussions on Cortés, Montaner and Muxí, Rolnik, Kern, and on Judith Butler’s debates about body controls and the precarious lives of the LGBTQIA+ population. The methodology adopted was descriptive, according to Serra and to Gil. As a result, we found a difficulty in continuing public policies dedicated to the LGBTQIA+ population, as well as an erasure of this population group in housing policies, in the face of constant harassment from neoliberal and far-right governments. Therefore, publicizing and encouraging recent inclusive experiences of sexual dissent can be a further step in promoting social rights.